Alarm System Using Body Detector - Noor Din, Ummi Kalsom (2008)
Nowadays, portable automatic intruder system has become very popular among security system. Body detector is a valuable technology tool that can be used to perform Alarm System Using Body Detector. Alarm system by using a body detector is an application for the smart alarm system because it relies only with the existence of electrical field that surrounds the human body. This alarm system adopts advanced RF oscillators matched with reliable software technology and advanced hardware circuitry. It integrates capacitance detection, network search, and automatic voice alarm. This system mainly uses capacitance detector, body intruding detection to transmit alarming signal to main unit. When signal is received, it processes it immediately, and then main unit will automatically give an alarm by the designed code. The idea behind this project is to solve the problem of traditional security method by using a non-portable alarm system due to excessive data transfer and complex hardware circuitry. Body detector security system makes all services that relate to information simpler, safer, cheaper and portable. In this project, a Microcontroller PIC16F877 will be used as an actuator of the system that will control the output system through a programming system. The system will be developed to control the system flow such as register data, delete data, and creating program flow to produce the output depends on the activation of body detector hardware circuitry. The PIC16F877 microcontroller will analyze and process the data and if the data has been registered in the system, the security application will work such as triggering the buzzer and LED.